2010
DOI: 10.7150/ijms.7.124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lumbar Facet Joint Nerve Blocks in Managing Chronic Low Back Pain: A Randomized, Double-Blind, Controlled Trial with a 2-Year Follow-Up

Abstract: Study Design: A randomized, double-blind, controlled trial.Objective: To determine the clinical effectiveness of therapeutic lumbar facet joint nerve blocks with or without steroids in managing chronic low back pain of facet joint origin.Summary of Background Data: Lumbar facet joints have been shown as the source of chronic pain in 21% to 41% of low back patients with an average prevalence of 31% utilizing controlled comparative local anesthetic blocks. Intraarticular injections, medial branch blocks, and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
241
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(253 citation statements)
references
References 64 publications
(52 reference statements)
6
241
0
3
Order By: Relevance
“…Thus, it is suggested that corticosteroids may be unnecessary for nerve root blocks. This concept has been reinforced by numerous randomized and observational studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A recent systematic review has found that there was no significant difference between transforaminal and caudal epidural injection [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that corticosteroids may be unnecessary for nerve root blocks. This concept has been reinforced by numerous randomized and observational studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A recent systematic review has found that there was no significant difference between transforaminal and caudal epidural injection [39].…”
Section: Discussionmentioning
confidence: 99%
“…20 The above-mentioned studies assessed the efficacy of facet joint injection in participants who had subacute or chronic back pain with various causes, and the results may not be applicable to our patients. [18][19][20] To the best of our knowledge, there is no study available in the literature that evaluates the efficacy of facet and/or SIJ injection in patients with persistent or recurrent back pain after vertebral augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature showed different results in pain relief after facet injection. [18][19][20] A randomized double-blind controlled trial with a 2-year follow-up showed a very high rate of significant pain relief in 85%-90% of patients with chronic back pain after lumbar facet injection. 18 However, another systematic review by Boswell et al 19 showed that the evidence for short-and long-term pain relief is moderate for lumbar facet joint injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is comprised of case reports and small case series, along with a few randomized, placebo-controlled trials (RCTs). For example, therapeutic lumbar facet joint nerve blocks can provide effective pain relief and functional improvement (Manchikanti et al, 2010). However, epidural corticosteroid injections for sciatica appear to offer only transient benefit (Arden et al, 2005).…”
Section: Interventional Therapiesmentioning
confidence: 99%